MABBACA DOANG: TRADISI MEMBACA DOA PADA MASYARAKAT BUGIS PERANTAUAN DI DESA TOMBEKUKU KECAMATAN BASALA KABUPATEN KONAWE SELATAN - Muh. Aking (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2018)
The research aims to find out the types of traditions of mabbaca doang in overseas Buginese communities, Tombekuku Village. In addition, it is also to find out the reasons for the local community still maintaining the tradition. The data analysis is descriptive qualitative. Data collections are observation techniques and in-depth interviews. The results of this study indicate that the tradition of mabbaca doang by the Bugis migrants in Tombekuku Village has several types, namely mabbaca doang when approaching fasting, during Eid al-Fitr, and have a new house. This tradition is carried out in various forms of gratitude by the local community towards the Almighty God. Besides this tradition, it also aims to obtain blessings, health, and safety in life. Socially, this tradition serves as a means to strengthen the kinship among communities. Whereas from the religious aspect, this tradition serves as a way of pleading to the Creator. The reason the Buginese community maintain the tradition of mabbaca on the overseas is that the tradition is a hereditary belief from the ancestors and to preserve the tradition in the overseas land. Keywords: traditions, mabacca doang, the overseas Buginese communities